Computer algebra and applications - Aleksas Domarkas; Rimantas-Jonas Rakauskas; Albertas Pincevičius (Lietuvos Matematikos Rinkinys)
Short review of computer algebra systems Macsyma, Maple, Derive, Mathematica, MuPad, Maxima.